Penerapan Model Contextual Teaching And Learning Untuk Meningkatkan Kemampuan Mendeskripsikan Fabel Pada Siswa Kelas VIII-6 SMP Negeri 2 Peusangan Bireuen - Nur Asma; Muhammad Insya (PTE FTK UIN Ar-Raniry, 2015)
The problem studied was how the application of the CTL model could improve the ability to describe a fable in Class VIII-6 of SMPN 2 Peusangan. This study aimed to improve the ability to describe a fable in the class through the CTL model. The benefit of this research included improving fable describing ability on Class VIII-6 students of SMP Negeri 2 Peusangan through the application of the CTL model. The approaches used in this study were the qualitative research and the Class Action Research (PTK). Data collected in the study came from the pre-test and post test, observation, interviews, and field notes. The results showed that the implementation of narrative essay writing with the CTL approach could increase the activities of teachers and students. The results of observations of the teachers and students activities in the implementation of the cycle I action obtained and average percentage of 80.4%. However, in terms of the results, the implementation of the first cycle of action had not been successful because the students obtained the value of â‰¥ 65 were 68.6%, with 56% of class completeness. Thus, the researcher conducted a repetition cycle. The results of observations of teachers and students in the second cycle of action earned the average percentage of 84.2%, and reached 88% of classical completeness. Moreover, in terms of the results, the implementation of the second cycle showed that teaching narrative essay writing by applying the CTL model could improve students' writing on the fable describing materials. This can be seen from the percentage of the students who received â‰¥ 65 classically were 88%, with the class average of 84.2. Therefore, the CTL model used could increase the activities of teachers and students in fable describing in Class VIII-6 students of SMP Negeri 2 Peusangan, Bireuen district. Kata Kunci: CTL, Fabel.